Effects of financial structure, preferential tax rate and tax incentives on dynamics of SMEs’ growth in Malaysia - Romli, Mohd Arif (2018)
In the new global economy, the role of small and medium enterprises (SMEs) in economic development has emerged as powerful platforms for a country’s growth policy. Leading world organizations such as the World Bank (WB) and the Organization for Economic Co-operation and Development (OECD) provide coherent policy framework that liberalisation in finance and special tax policies for SMEs holds the key to economic growth, innovation, poverty alleviation and redistribution. The same policy is practiced in Malaysia where SMEs are supported by diverse financing programs, preferential tax rate (PTR) and tax incentives to support their growth. However, limited is known on the current situation of SMEs in term of their financial structure and the efficacy of tax policy implemented in Malaysia. In addition, revenue forgone from tax policy implemented reduces billions of government’s spending power is akin to government expenditures and entails risk of unproductive spending if the tax programs are not effective. From that perspective, the study aims to achieve three objectives using the system generalized method of moments (GMM) as the main estimation technique. Firstly, the study investigates the role of financial structure to the growth of SMEs. Secondly, the study assesses whether preferential tax rate (PTR) supports the growth of SMEs and third, the study evaluates whether tax incentives enjoyed by SMEs are pro-growth policies in Malaysia. Data in this study are retrieved from confidential Malaysian corporation tax returns for the period of 2006 - 2015. The sample of firms in this paper follows the definition of SMEs under the Malaysian Income Tax Act (ITA) 1967. Therefore, only corporate small and medium firms are analysed in this study. The sample of SMEs are then categorized by two groups, namely the users and non-users of tax incentives so that the financial structure and the effect of SME tax policy can be compared between these two groups. The study contributes to the literature in three important ways. Firstly, unlike previous studies that use other definitions of SMEs, this study used the definition under ITA 1967 and gives evidence on the importance of financial structure and effectiveness of SMEs tax policy to firm growth. Secondly, unlike previous studies that give evidence on the importance of cash flow and debt to SMEs growth, the findings also give significant contributions on the importance of financial structure between the users and non-users of tax incentives. Furthermore, on the financial structure of SMEs, external finance is comparably important to SMEs growth that may give evidence access to finance is not an issue for SMEs in this study. Thirdly, unlike previous studies that uses dummy variable to evaluate the effectiveness of PTR and tax incentives, this study uses quantifiable variable to measure the tax advantage received by SMEs. Moreover, this study gives empirical evidence on the effectiveness of PTR to the users and non-users of tax incentives that little is known on the importance of PTR to these groups. The findings revealed that on the aspect of financial structure, cash flow as the proxy of internal finance is slightly more sensitive to firm growth than debt which is a proxy of external finance. This provides evidence that internal finance is more important than external financing. Furthermore, internal finance is more important for the non-users of tax incentives while external finance is more important to users of tax incentives. PTR and tax incentives as part of external finance to SMEs are found to be pro-growth policies. Specifically, PTR as the main policy for SMEs promotes growth in sales and assets of SMEs. Comparison of the importance of PTR between the users and non-users of tax incentives is that PTR is more sensitive to the growth of non-users of tax incentives. For tax incentives, even though they promote the growth of sales, but the findings show that at the same time they discourage the growth of asset of the users of tax incentives. Finally, the crucial implication of this study to policy makers is monitoring and controlling the effectiveness of tax policy through tax expenditure reporting is the key in reducing government budget deficit and the risk of unproductive tax policy. This study indicates that preferential policy can give positive impact to focused group and, it alleviates firms from relying more on internal finance which indicates that external finance is reachable by SMEs and it also reduces taxation pressure due to the tax advantage from PTR and tax incentives. Hence, given the advantage of SMEs, other preferential programs specifically designed and monitored could give positive effect to SMEs and aggregately to the growth of a country.